CO2 activation and synthesis of cyclic carbonates and alkyl/aryl carbamates over adenine-modified Ti-SBA-15 solid catalysts - Srivastava, R; Srinivas, D; Ratnasamy, P (Journal of Catalysis, 2005)
Cyclic carbonates were synthesized by the cycloaddition Of CO2 to epoxides (epichlorohydrin, propene oxide, and styrene oxide), and carbamates were synthesized by reaction of alkyl or aryl amines, CO2, and n-butyl bromide. Solvents and cocatalysts/promoters, like N,N-dimethylaminopyridine (DMAP) and quaternary ammonium salts, which are usually essential with conventional catalyst systems, could be avoided with the use of adenine-modi lied Ti-SBA-15 catalysts. The catalysts were reused in several recycle experiments. The structural and textural properties of the catalysts were determined by X-ray diffraction (XRD), transmission electron microscopy (TEM), N-2 adsorption, and Fourier transform infrared (FTIR) and diffuse reflectance ultraviolet-visible (UV-vis DRS) techniques. Acid-base properties of the solid catalysts were investigated by temperature-programmed desorption (TPD) of NH3 and CO2 and DRIFTIR spectroscopy of adsorbed pyridine and CO2 techniques. The studies reveal that the Ti4+ ions increase catalytic activity by enhancing the adsorption of the epoxide and alkyl or aryl amine substrates. CO2 molecules are activated at the basic nitrogen groups of adenine. Increasing the surface concentrations of either CO2 (by anchoring basic molecules like adenine or increasing the partial pressure of CO2) or epoxides and alkyl or aryl amines (by increasing the concentration of Lewis acidic Ti4+ ions) enhances the catalytic activity. CO2 molecules activated at the covalently anchored adenine sites react with epoxide/amines adsorbed on the silica surface to form carbonates/carbamates. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activation of CO2; CO2 fixation; DRIFTIR spectroscopy of adsorbed pyridine and CO2; organo-functionalized mesoporous silica; phosgene-free synthesis; synthesis of carbamates; synthesis of cyclic carbonates; temperature-programmed desorption of NH3 and CO2 titanosilicates; Ti-SBA-15

Ti-oxo radicals and product selectivity in olefin oxidations over titanosilicate molecular sieves - Shetti, VN; Srinivas, D; Ratnasamy, P (Zeitschrift für Physikalische Chemie International Journal of Research in Physical Chemistry and Chemical Physics, 2005)
The O-O bond of Ti-oxo species (Ti-peroxo, Ti-hydroperoxo or Ti-superoxo) generated on titanosilicate molecular sieves contacted with H2O2 cleaves either heterolytically or homolytically. While the former type of O-O cleavage (generating non-radical reactive oxygen intermediates) leads to selective epoxide products, the latter (generating reactive oxygen radical intermediates, O-2(-center dot) and HOOcenter dot) results in non-sclective, allylic oxidation products in cyclohexene oxidation. These radicals were detected using EPR spin trapping techniques 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as the spin trap. Radical quenchers like hydroquinone suppressed their concentration and enhanced epoxide selectivity.
Keywords: cyclic voltammetry of titanosilicates; EPR-spin trap experiments; Molecular sieves; oxidations; product selectivity; reactive oxygen species; titaniunz-oxo radicals; Titanosilicates

Zeolite-based organic-inorganic hybrid catalysts for phosgene-free and solvent-free synthesis of cyclic carbonates and carbamates at mild conditions utilizing CO2 - Srivastava, R; Srinivas, D; Ratnasamy, P (Applied Catalysis A - General, 2005)
As-synthesized zeolite-beta exhibits high catalytic activity for the synthesis of cyclic carbonates and alkyl and aryl carbarnates by a phosgene-free route, utilizing the greenhouse effect gas CO2. The reaction occurs with high yields of the desired products at mild conditions and without using any solvent or cocatalyst. Cyclic carbonates are synthesized by cycloaddition reaction Of CO2 with oxiranes (epichlorohydrin, propene oxide, styrene oxide and n-butene oxide) at 393 K and 6.9 bar. Alkyl and aryl carbarnates are synthesized by the reaction of the corresponding amines, CO2 and n-butyl bromide at 353 K and 3.4 bar. The as-synthesized zeolite-beta containing the encapsulated quaternary ammonium ions is not only reusable in several recycling experiments, but also shows superior activity to that of the corresponding homogeneous, quaternary ammonium halide salt generally used in the commercial synthetic practice. The microporous silica (inorganic) acting in concert with the encapsulated organic component constitutes an efficient, recyclable catalyst for this reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyl and aryl carbamates; carbon dioxide utilization; cyclic carbonate; phosgene-free synthetic route; Polycarbonate; zeolite-beta